ANALISIS PEMASARAN SEMANGKA DI DESA MARANATA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Yusnia, Yusnia; Muis, Abdul; Sulaeman, Sulaeman (AGROTEKBIS, 2017)
This study aims to determine the form of marketing channels, the amount of margin marketing, part of the price received by farmers and commodity marketing efficency of watermelon in the MaranataVillage Subdistrict of Sigi Biromaru Sigi District. The based on the results of research showed that there are two marketing channels in the Maranata Village. Local marketing margin watermelon obtained for the first channel IDR 2,000 and total marketing margin watermelon hammer obtained for the second channel is IDR 1,500. The parts of prices received by farmers in the first line channel 42%. The any part of the price received by farmers in the second channel 57%. The value of marketing efficiency of channel I was 58% and for channel II by 43%.From both the efficiency of the channels I and II of the most efficiency is channel II. Key words: Efficiency, marketing, margin, watermelon